1999
DOI: 10.1521/pedi.1999.13.3.287
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Examination of Borderline Personality Disordered (BPD) Patients: Interpersonal Dynamics and Underlying Paradoxes

Abstract: Theoretical conceptualizations of symptomatology in patients with borderline personality disorder (BPD) have noted an inability to integrate contradictory perceptions (splitting, or dichotomous thinking) as a hallmark of the disorder. This study investigated contradictions manifest in the thinking and behavior of BPD patients, using the concept of paradox. A paradox occurs when an apparent contradiction contains an underlying logic which makes the contradiction comprehensible. Using qualitative methods of anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…This theme reflected a paradoxical combination of a yearning for closeness and connection, conflicting with a strong fear of intimacy [ 36 , 63 , 73 , 74 , 76 , 78 , 86 , 87 ]. This simultaneous conflicting pull for closeness and distance was very challenging for participants to resolve.…”
Section: Resultsmentioning
confidence: 99%
“…This theme reflected a paradoxical combination of a yearning for closeness and connection, conflicting with a strong fear of intimacy [ 36 , 63 , 73 , 74 , 76 , 78 , 86 , 87 ]. This simultaneous conflicting pull for closeness and distance was very challenging for participants to resolve.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies on evaluations by patients with BPD (Arntz & Veen, 2001;De Bonis, De Boeck, Lida-Pulik, Hourtane´, & Fe´line, 1998;Leichsenring, Roth, & Meyer, 1992;Sheffield et al, 1999;Veen & Arntz, 2000) support the hypothesis that DT is prominent in BPD. Overall, it was found that borderline patients evaluated others more extremely than clinical and nonclinical controls.…”
Section: Introductionmentioning
confidence: 95%
“…It is assumed that split evaluations (1) are unidimensional or univalent, i.e., all good or all bad, and (2) can be extremely positive (idealization) as well as extremely negative (devaluation). Studies focusing on interpersonal evaluations found evidence for both unidimensional DT (Arntz & Veen, 2001), as well as multidimensional or multivalent (for example, very good and very bad) DT (De Bonis et al, 1998;Sheffield et al, 1999;Veen & Arntz, 2000). According to Arntz and Veen (2001), response format might explain these ambiguous findings.…”
Section: Introductionmentioning
confidence: 99%
“…ity Disorders)中文版本 [11] [13] 和 Linehan [14] 的观点, 即边缘型人格障碍的决定性特征是分裂(splitting)的 防御机制的使用。但不同的是,分裂的防御机制是指 把世界看成或者全好或者全坏,而在沙盘中,分裂更 多地表现为不相干的、矛盾的、对立的东西同时出现, 并且没有得到很好的整合,没有协调统一起来,仅仅 是"在一起" 。Sheffield 等 [15] 提出了"悖论"(paradox)…”
Section: 边缘人格在沙盘中的表现及其病理模型 和内心世界模型unclassified